Back Cover: Intramolecular Frustrated Lewis Pair with the Smallest Boryl Site: Reversible H2 Addition and Kinetic Analysis (Angew. Chem. Int. Ed. 6/2015). Issue 6 (14th January 2015) - Chernichenko, Konstantin; Kótai, Bianka; Pápai, Imre; Zhivonitko, Vladimir; Nieger, Martin; Leskelä, Markku; Repo, Timo
<x xml:space="preserve">Abstract</x> An ansa‐aminoborane an intramolecular frustrated Lewis pair with the smallest Lewis acidic boryl site (BH2), predominantly exists in quenched dimeric form in solution. A monomeric species accountable for hydrogen activation is also present in equilibrium. In their Communication on page 1749 ff., I. Pápai, T. Repo et al. describe the reactivity of this frustrated Lewis pair towards H2 and the corresponding reaction mechanism.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>